2020
DOI: 10.1186/s13054-020-02963-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanical power on intensive care mortality in ARDS patients

Abstract: Background: In ARDS patients, mechanical ventilation should minimize ventilator-induced lung injury. The mechanical power which is the energy per unit time released to the respiratory system according to the applied tidal volume, PEEP, respiratory rate, and flow should reflect the ventilator-induced lung injury. However, similar levels of mechanical power applied in different lung sizes could be associated to different effects. The aim of this study was to assess the role both of the mechanical power and of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
93
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 50 publications
(67 reference statements)
4
93
0
2
Order By: Relevance
“…We compared C-ARDS patients with 247 consecutive ‘other ARDS’ patients enrolled in previous and ongoing studies (NCT03920189). 8 The Institutional Ethics Board of ASST Santi Paolo e Carlo, San Paolo University Hospital, Milan, Italy approved the study, and the Institutional Ethics Board of Fondazione IRCCS Ca’ Granda Ospedale Maggiore Policlinico, Milan, Italy approved this study for Maggiore Hospital, Lodi, Italy. The datasets used, analysed, or both during the current study are available from the corresponding author upon reasonable request.…”
mentioning
confidence: 99%
“…We compared C-ARDS patients with 247 consecutive ‘other ARDS’ patients enrolled in previous and ongoing studies (NCT03920189). 8 The Institutional Ethics Board of ASST Santi Paolo e Carlo, San Paolo University Hospital, Milan, Italy approved the study, and the Institutional Ethics Board of Fondazione IRCCS Ca’ Granda Ospedale Maggiore Policlinico, Milan, Italy approved this study for Maggiore Hospital, Lodi, Italy. The datasets used, analysed, or both during the current study are available from the corresponding author upon reasonable request.…”
mentioning
confidence: 99%
“…Zhang et al reported that MP normalized to PBW was far more accurate than the absolute value of MP in predicting mortality [6]. Coppola et al reported no causal relationship between MP alone and mortality, whereas both MP and transpulmonary MP normalized to respiratory system compliance or to the amount of well-aerated tissue were independently associated with ICU mortality [7]. However, the above studies were predicated on baseline MP values, they did not account for serial changes in MP during the ICU stay and did not seek to determine whether the link between MP and mortality was independent from other ventilator settings.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that those patients were not fully sedated and paralyzed, and neuromuscular blocking agents were used in only 41 % of cases [15]. In estimating MP values, patients should be completely relaxed; i.e., without any active inspiratory efforts [7]. In our study, the median spontaneous RR before ECMO was 0 (0-7) breaths/minute and 1 (0-4) breath/minute during the rst 3 days of ECMO, indicating that our patients were nearly total sedated and paralyzed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations